OH! IDE, BACANTES!: a participação feminina em rituais dionisíacos - Rodrigues, Amanda Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Female history in Greek antiquity, although defined by women’s isolation to domestic spaces and exclusion from social and political environments, can be outlined by female participation in religious practices, which, in turn, integrated a significant part of the city’s customs and structure. The aim of the project, considering women’s participation in the cult of Dionysos, is to investigate to what extent Dionysiac possession rituals are capable of granting authority to the participants, subverting, or not, their social status. To achieve this, I intend to examine the practices associated with the rites, verifying their historical accuracy and debating Euripides’ The Bacchae’s reliability in authentically portraying the rituals throughout the poetic text

A história feminina na antiguidade grega, marcada pelo isolamento das mulheres em aposentos domésticos e por sua exclusão de ambientes políticos e sociais, pode ser traçada a partir da participação feminina em práticas religiosas que integravam grande parte dos costumes e do funcionamento da cidade. O objetivo deste projeto, portanto, partindo da participação das mulheres no culto ao deus Dioniso, é investigar em que medida os rituais dionisíacos de possessão são capazes de oferecer autoridade às participantes, subvertendo, ou não, seu posicionamento social. Para isso, pretende-se examinar práticas associadas aos ritos, verificando sua veracidade histórica e discutindo a confiabilidade da peça As Bacantes, de Eurípides, para retratar autenticamente a imagem do ritual no texto poético.
OH! GO, BACCHAE!: female participation in dionysiac rituals
Keywords: Rituals; Dionysos; Female History; The Bacchae; Euripides; Religion; Maenadism; Rituais; Dioniso; História Feminina; Bacantes; Eurípides; Religião; Menadismo